A political economy of the Poor People’s Campaign: From MLK and Polanyi to Trump - Callebert, Ralph; Soni, Raji Singh (Sikh Formations, 2018)
A stalemate has emerged in mainstream liberal/left responses to Trump. Many commentators prefer to see our predicament in terms of either class-based or identity politics. Vis-à-vis the influence of the Chicago school of economics and its structural adjustment schemes, we crosshatch MLK’s Poor People’s Campaign and Polanyi’s Great Transformation to envision overcoming this stalemate. King’s effort to radicalize the welfare state from below by linking struggles against poverty, racism, and imperialism shares Polanyi’s focus on the economy’s embeddedness in society. We underscore the importance of King’s and Polanyi’s visions for building a leftist coalition that does not divorce social from economic justice.
History; Religious Studies
Keywords: Great Transformation; The (Book); KING; Martin Luther; Poor People's Campaign; TRUMP; Donald; embeddedness

Ritual Matters: Changing Ontologies, Values, and Ecological Conscience Formation - Davy, Barbara Jane; Quilley, Stephen (Journal for the Study of Religion, Nature & Culture, 2018)
Karl Polanyi (1944, 1968) argued that the 'disembedding' of the economy from society entailed a curtailment of social constraints on economic transactions. This disembedding coincided with what Max Weber (1946) called disenchantment, and the erosion of cognitive-experiential reciprocity between humans and nature. Following Lynn White Jr. (1967), many scholars of religion and ecology have argued that losing the sense of divinity immanent in the world caused the modern devaluation of nature. But the loss of ritual practices is key to this. Integrating Roy Rappaport's (1968, 1979, 1999) understanding of the regulative ecological functions of ritual with a processual understanding of ontology following Norbert Elias (1939, 1978, 1989) suggests that reviving ritual gifting practices may be a vehicle for ecological conscience formation and the social-ecological transformation of modern society. Removing the rituals surrounding the giving of gifts removed crucial informal governance structures from pre-modern cultures, resulting in a general collapse of meaning structures in modern market societies, producing a pervasive individualized ontology and what Elias (1991) called 'the society of individuals'. A revival of ritual gifting practices that re-enchant human relations with other than human persons, such as found in what Graham Harvey (2006, 2016) has called 'the new animism', may revive relational ontology and shift modern society toward a more sustainable path by re-embedding the economy in society.
Environmental Studies; Religion Studies
Keywords: POLANYI; Karl; 1886-1964; animism; ecological conscience formation; ecology - religious aspects; environmental behaviour; gift economy; informal governance; new animism; ontology; relational ontology; religion and ecology; ritual; systems theory; systems thinking